Actor and Goal Representation in the Transitivity System of Undergraduate Theses and Journal Research Articles: an SFL Perspective - Marsandi Manar; Siti Wachidah; Ratna Dewanti (Loquen, 2020)
AbstractThe current study scrutinizes the representation of actors and goals of transitivity system in the introduction sections of theses (ISoT) composed by undergraduate students in reference to that of the introduction sections of research articles (ISoRA) considered as the target writings in the academic discourse of knowledge building. 738 English ranking clauses from 10 English-field ISoT and 694 from 10 ISoRA of TESOL Quarterly were analysed for their material processes as well as their participants and circumstances. The analysis was executed with the tables of analysis adapted from Halliday’s experiential meaning framework. The analysis reveals that in the material processes of ISoRA previous studies and previous researchers instead of current studies and current researchers are more frequently employed as actors. Contrary, in their ISoT counterpart, the latter outnumber the former. The analysis also finds that goals in the material processes of ISoT in comparison with its ISoRA counterpart still lack previous findings. Overall, the representation of actors and goals in the material processes of ISoT still needs lexical resources that underpin the process of knowledge building. This has been confirmed by the tendency of actors and goals of ISoT to represent its study undertaken, compared with its ISoRA counterpart focusing more on previous related studiesKeywords: actors, goals, material process, transitivity system, ISoT, ISoRA